2003
DOI: 10.1379/1466-1268(2003)8<76:miaeoh>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and expression of heat shock cognate 70 (hsc70) and heat shock protein 70 (hsp70) genes in the Pacific oyster Crassostrea gigas

Abstract: The 70-kDa heat shock protein (Hsp) family is composed of both environmentally inducible (Hsp) and constitutively expressed (Hsc) family members. We sequenced 2 genes encoding an Hsp70 and an Hsc70 in the Pacific oyster Crassostrea gigas. The Cghsc70 gene contained introns, whereas the Cghsp70 gene did not. Moreover, the corresponding amino acid sequences of the 2 genes presented all the characteristic motifs of the Hsp70 family. We also investigated the expression of Hsp70 in tissues of oysters experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 47 publications
2
63
1
1
Order By: Relevance
“…Furthermore, more recent evidence showed that HSPs are involved in the cell response to most environmental and physiological stressors (reviewed by Wegele et al 2004). This includes studies in molluscs (CruzRodriguez et al 2000;Snyder et al 2001;Boutet et al 2003;Piano et al 2004). Here again, semi-quantitative methods were used to obtain evidence for an increase in various stressing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more recent evidence showed that HSPs are involved in the cell response to most environmental and physiological stressors (reviewed by Wegele et al 2004). This includes studies in molluscs (CruzRodriguez et al 2000;Snyder et al 2001;Boutet et al 2003;Piano et al 2004). Here again, semi-quantitative methods were used to obtain evidence for an increase in various stressing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the amino acid sequences comparison, Piano et al [36] pointed out that the GGMP repeats are present in the bivalve constitutive heat shock cognate 70 (Hsc70), while absent in the inducible heat shock protein 70 (Hsp70), as seen between mammalian Hsc70 and Hsp70 [17]. In the pacific oyster C. gigas and European flat oyster O. edulis, however, both of Hsp70 and Hsc70 contained two repeats of GGMP tetrapeptide [43,44]. In the present study, the deduced amino acid sequence of PFHsp70 lacks the GGMP tetrapeptide repeats, which is in agreement with previous study in the mediterranean mussel, Mytilus galloprovincialis [45].…”
Section: Discussionmentioning
confidence: 99%
“…2). Amino acid sequence analysis indicated that Xc-HSC70 and Xc-HSP70 contained the cytoplasmic characteristic motif EEVD (Boutet et al 2003) and 3 signature sequences of the HSP70 family ( Figs. 1 and 2).…”
Section: Nucleotide Analysis and Deduced Amino Acid Sequences Of Xc-hmentioning
confidence: 99%
“…encoded by 2 different genes, constitutive type HSC70 (heat shock cognate 70) and inducible type HSP70 (Boutet et al 2003;Deane & Woo 2005;Franzellitti & Fabbri 2005). In normal conditions, HSC70 is constitutively expressed in all cells, whereas HSP70 is not expressed or is expressed only at a low level.…”
mentioning
confidence: 99%